Thallium stable isotope fractionation in white mustard: Implications for metal transfers and incorporation in plants - Vaněk, Aleš; Holubík, Ondřej; Oborná, Vendula; Mihaljevič, Martin; Trubač, Jakub; Ettler, Vojtěch; Pavlů, Lenka; Vokurková, Petra; Penížek, Vít; Zádorová, Tereza; Voegelin, Andreas (Journal of hazardous materials, 2019)
We studied thallium (Tl) isotope fractionation in white mustard grown hydroponically at different Tl doses. Thallium isotope signatures in plants indicated preferential incorporation of the light 203Tl isotope during Tl uptake from the nutrient solution. Negative isotope fractionation was even more pronounced in dependence on how much the available Tl pool decreased. This finding corresponds to the concept of isotope overprinting related to a high contamination level in the growing media (solution or soil). Regarding Tl translocation in plants, we observed a large Tl isotope shift with an enrichment in the heavy 205Tl isotope in the shoots relative to the roots in treatments with low/moderate solution Tl concentrations (0.01/0.05 mg Tl/L), with the corresponding α205/203Tl fractionation factors of ˜1.007 and 1.003, respectively. This finding is probably a consequence of specific (plant) reactions of Tl replacing K in its cycle. The formation of the S-coordinated Tl(I) complexes, potentially affecting both Tl accumulation and Tl isotope fractionation in plants, however, was not proven in our plants, since we did not have indication for that on the basis of X-ray absorption spectroscopy, suggesting that Tl was mainly present as free/hydrated Tl+ ion or chemically bound to O-containing functional groups.
Keywords: Plant; Plant Leaves; Radioactive Pollutants; Thallium Radioisotopes; Algorithms; Metals; Mustard Plant; hořčice rodu Brassica; Isotopes; kovy; listy rostlin; biomasa; Isotope fractionation; Plant Shoots; kořeny rostlin; radioaktivní znečišťující látky; výhonky rostlin; radioizotopy thallia; algoritmy; Brassica; Thallium; Plant Stems; thallium; Biomass; Plant Roots; stonky rostlin